The new map of injuries in the aftermath of the COVID-19 pandemic: examples from north with south Europe. (20th October 2021) - Alves, T; Lund, J; Papadakaki, M
Abstract: The aim of this paper is to describe the impact of the pandemic on injuries. Data from National Injury Surveillance System of Norway and Portugal during Covid-19 period were analyzed. In Norway hospital data on injury diagnoses were collected from a national emergency preparedness register established during the pandemic. The number of injured patients per day in the period 1 January-30 June 2020 were identified. The change in patient volumes over two three-week periods before and during the lockdown by sex, age, level of care, level of urgency, type of contact and type of injury were analysed. In Portugal we described the temporal trend in 2020 of the Home and Leisure Accidents(HLA) among vulnerable groups(0-19years, 65years+), who needed attendance in Emergency Department(ED) of the National Health Service Hospitals. In 2019 and 2020, 240 538 HLA episodes were recorded in the age groups of interest. In Norway, there was an overall reduction of 43% in injured patients during the first three weeks of lockdown. The decrease in patient contacts did not differ by sex, but was most pronounced among young people. Substantial reductions were observed for both acute and elective treatment and across all levels of care and types of contact, with the exception of indirect patient contacts. The change in patient contacts varied considerably by injury type, with the largest reduction observed for dislocations/sprains/strains and a lower decrease for burns/corrosions/poisoning. Similar trend was observed in Portugal on home and leisure accidents episodes rate registered in children and young people up to 19 years decreased by 24, 0% during the 2020 year. In groups of 10-14 years the greatest significant decrease of 35, 2% was observed, followed by groups of 5-9 years with a decrease of 24, 1%. In 65-74 years an increase of 13, 2% was recorded, with the highest increase(19, 1%) among people aged 75+. Implications for the health systems and health policy planning will be discussed.